Complications Encountered in Management of Femur Fractures in Dogs using String of Pearls (SOP) Locking Plate System with or without Intramedullary Pinning - Kumari, Anita; Bishnoi, P; Bishnoi, A K; Palecha, Sakar; Kumar, Raj (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was performed in 16 clinical cases of femur fractures in dogs. The cases were divided into two groups A and B. In Group-A femur fracture was stabilized with SOP locking plate system alone, while in Group-B femur fracture was stabilized with plate-rod construct using SOP locking plate and intramedullary (IM) pin.  Complications during post-operative period were observed in 8 out of 16 animals, out of which the single complication was seen in 5 cases, while multiple complications were encountered in 3 cases. The commonest complications recorded were plate breakage (3 cases), screw loosening and bone splitting (3 cases), deformity of bone (1 case), demineralization of bone (1 case) and IM pin migration (1 case). The complications were less in Group B, where the fractures were stabilized with SOP and IM pin construct.
Keywords: Complications; Femur fracture; IM pin; Screws; String of Pearls (SOP) locking plat